Efciency of Anti-Epidemic Measures that Ensure Access to Work in Rotational Shifts under Conditions of Covid-19 Pandemic - A. Yu. Popova; E. B. Ezhlova; Yu. V. Demina; A. A. Mel’nikova; O. P. Kurganova; N. N. Fomkina; O. M. Yurgina; E. N. Burdinskaya; O. E. Trotsenko; A. A. Totolyan; T. V. Korita; E. A. Bazykina; et al. (Проблемы особо опасных инфекций, 2021)
Objective – integral analysis of eﬀectiveness of anti-epidemic measures applied towards employees of the Amur gas processing plant assigned for rotational work under conditions of COVID-19 pandemic.Materials and methods. Sero-epidemiological study included a questionnaire survey of 1461 workers who arrived through the “clean corridor” in the Amur Region, followed by sampling of biological material (blood and respiratory smears). Testing of blood sera for the presence of antibodies to SARS-CoV-2 of two classes (IgM and IgG) was carried out applying enzyme immunoassay. Using PCR, respiratory smears were examined for the presence of the agent RNA in them. Statistical processing of the results obtained was carried out using conventional methodsResults and discussion. The presence of antibodies of the IgG class was revealed in (4.7±0.55) % of cases. In a small cohort (1.7±0.34 %) of practically healthy individuals, asymptomatic infection was detected, confrmed either by a positive PCR result (0.76±0.23 %), or by the detection of IgM antibodies (1.0±0.08 %). On the basis of the study carried out by the Federal Service for Surveillance in the Sphere of Consumer Rights Protection and Human Welfare on August 01, 2020, “Temporary recommendations on the procedure for admitting to work on a rotational basis under the risk of COVID-19 spread in the Amur Region” were approved. These recommendations set out the algorithm for observation of incoming workers and the order for triage of shift workers after testing by ELISA and PCR. The results of the study demonstrate the eﬀectiveness of anti-epidemic measures related to ensuring the procedure for admission to work on a rotational basis under the risks of the spread of COVID-19.